Marginal microleakage in Bulk Fill resins - NASCIMENTO,Armiliana Soares (2016)
Abstract Introduction Despite advances and innovations in restorative dentistry, microleakage remains one of the main problems in this area. Objective To evaluate in vitro marginal microleakage of Bulk Fill resins in class II cavities, with cervical termination in the dentin. Material and method Cavities, standardized on the mesial and distal surfaces, were prepared in forty top molars and randomly assigned to four groups (n = 10), according to the resin used. G1 (control): Filtek Z350 (3M/ESPE); G2: Filtek Bulk Fill flow (3M/ESPE); G3: Surefill SDR (Dentsply); G4: X-tra (Voco). These were further subdivided into subgroups according to the strategy used to apply the adhesive (self-etch technique and conventional). After storage for 24 hours in an oven (37 °C), the samples were submitted to the thermocycling test (500 cycles: 5 °C/55 °C). They were later waterproofed, immersed in Basic Fuchsin (0.5%) and sectioned in the mesial-distal direction for evaluation using a stereo magnifying glass at 40X (Coleman) Scores from 0 to 3 were assigned according to the microinfiltration observed. The Mann-Whitney and Kruskal-Wallis tests, with a significance level of 5%, were used for statistical analysis. Result There was no statistically significant difference between the Bulk Fill resins when the total acid-etching technique was used. Only the Filtek Bulk fill flow resin presented statistically significant results when the application of the adhesive system strategy was considered, with worse results, in relation to other groups, when it the self-etching strategy was considered. Conclusion The degree of leakage of the bulk fill resins studied, in class II cavities, was not influenced by the method of application of the adhesive system (conventional or two-step self-etching bonding agent), except for the Filtek Bulk fill flow.